2021
DOI: 10.3390/agronomy11102052
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Changes in Loam Soils Amended with Bamboo Biochar and Their Influence in Tomato Production Yield

Abstract: Soil degradation and water stress in Costa Rica challenge the production of highly sensitive crops. This work is aimed at evaluating the physical and chemical changes in sandy loam (SL) and a silt loam (SiL) soil when amended with bamboo biochar while estimating the enhancement of tomato productivity. Biochar, obtained from Guadua Angustifolia bamboo feedstock, was mixed into sieved bulk soil substrate from the topsoil, from Andosol and Umbrisol groups, at application rates of 1, 2.5, and 5% (dry mass). Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Liu et al (2021) mentioned that biochar application at rate of 2% increased available N, P, and K by 24, 37, and 19%, respectively, to be uptake by roselle plants. Similar results were obtained by Guo et al (2020), Villagra-Mendoza et al (2021, Zheng et al (2021).…”
Section: Discussionsupporting
confidence: 89%
“…Liu et al (2021) mentioned that biochar application at rate of 2% increased available N, P, and K by 24, 37, and 19%, respectively, to be uptake by roselle plants. Similar results were obtained by Guo et al (2020), Villagra-Mendoza et al (2021, Zheng et al (2021).…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, Guo et al reported yield improvements of up to 60% when using application rates of 30, 50, and 70 t/ha, fundamentally due to biochar interference in the fixation of supplemented nutrients and nutrient exchange in the soil-plant system [55]. In these temperate zones, other authors have reported results ranging from no improvement to slight improvements of 10% in tomato yield [56,57].…”
Section: Biochar Effect On Tomatomentioning
confidence: 99%
“…By the application of BBCs to soil obtained by the combustion of bamboo feedstocks, the quality and performance of different plants were enhanced. Particularly, the growth of mustard plants [ 194 ] and the yield of pakchoy plants [ 145 ], as well as the growth of tomato plants and the quality of their fruits, were improved [ 146 , 147 ]. Villagra-Mendoza et al reported that the physicochemical changes that occurred in loam soils amended with BBC obtained by the pyrolysis of bamboo stems at 400 °C determined a significant improvement in tomato production yield [ 147 ].…”
Section: Bamboo-derived Biochar (Bbc)mentioning
confidence: 99%
“…Particularly, the growth of mustard plants [ 194 ] and the yield of pakchoy plants [ 145 ], as well as the growth of tomato plants and the quality of their fruits, were improved [ 146 , 147 ]. Villagra-Mendoza et al reported that the physicochemical changes that occurred in loam soils amended with BBC obtained by the pyrolysis of bamboo stems at 400 °C determined a significant improvement in tomato production yield [ 147 ]. Wang et al demonstrated that the application of 5% bamboo biochar to soil reduced Cu uptake in the roots of Moso bamboo ( Phyllostachys pubescens ) and ameliorated soil physical properties and heavy metal solubility in soil [ 148 ].…”
Section: Bamboo-derived Biochar (Bbc)mentioning
confidence: 99%